Effect of concomitant vitamin D deficiency or insufficiency on lumbar spine volumetric bone mineral density and trabecular bone score in primary hyperparathyroidism. Issue 10 (October 2016) - Walker, M.; Saeed, I.; Lee, J.; Zhang, C.; Hans, D.; Lang, T.; Silverberg, S.
Abstract Summary Lower vitamin D and higher parathyroid hormone (PTH) levels are associated with higher volumetric BMD and bone strength at the lumbar spine as measured by central quantitative computed tomography in primary hyperparathyroidism (PHPT), but there are no differences in bone microarchitecture as measured by trabecular bone score (TBS). Introduction The purpose of this study was to evaluate the association between 25-hydroxyvitamin D (25OHD) and volumetric bone mineral density (vBMD) and the TBS at the lumbar spine (LS) in PHPT. Methods This is a cross-sectional analysis of PHPT patients with and without low 25OHD. We measured vBMD with quantitative computed tomography (cQCT) and TBS by dual-energy X-ray absorptiometry (DXA) at the LS in 52 and 88 participants, respectively. Results In the cQCT cohort, those with lower vitamin D (<20 vs. 20-29 vs. ≥30 ng/ml) tended to be younger (p = 0.05), were less likely to use vitamin D supplementation (p < 0.01), and had better renal function (p = 0.03). Those with 25OHD <20 ng/ml had 80 and 126 % higher serum PTH levels respectively vs. those with 25OHD 20–29 ng/ml (p = 0.002) and 25OHD ≥30 ng/ml (p < 0.0001). Covariate-adjusted integral and trabecular vBMD were higher in those with 25OHD 20–29 vs. those with 25OHD ≥30 ng/ml, but those with 25OHD <20 did not differ. Because there were few participants with 25OHD deficiency, we also compared those with vitamin D <30 vs. ≥30 ng/ml. Covariate-adjusted integral and trabecular vBMD were 23 and 30 % higher respectively (bothp < 0.05) in those with vitamin D <30 vs. ≥30 ng/ml. TBS was in the partially degraded range but did not differ by vitamin D status. Conclusion In mild PHPT, lower 25OHD is associated with higher PTH, but vitamin D deficiency and insufficiency using current clinical thresholds did not adversely affect lumbar spine skeletal health in PHPT. Further work is needed to determine if higher vBMD in those with lower vitamin D is due to an anabolic effect of PTH.